Malaysian diet : THE PLAIN TRUTH - Tee, E. Siong, author (Kuala Lumpur : University of Malaya Press, 2015)
In this book, leading Malaysian nutritionist Dr Tee E Siong reveal the plain truth about the Malaysian makan-makan culture. He provide insights into the meals we consume at breakfast, lunch, dinner, snack and suppertime. The author expose the gory consequences of unhealthy eating. He will convince that unhealthy diet is a major cause of chronic disease like obesity, heart disease, diabetes and cancers. And that there is only one way to prevent these diseases which is by practicing health eating and active living. He shared the basic principles of healthy eating and guide on how to apply good nutrition in our daily lives. By reading this book, you will find that it is possible to adopt a healthier makan culture while enjoying the goodness of Malaysian food.